Evaluation of the disability-friendly sexual violence prevention and response program in Sragen Regency - Ismi Dwi Astuti Nurhaeni; Asal Wahyudi Erlin Mulyadi; Sajida Sajida; Rina Herlina Haryanti; Desiderius Priyo Sudibyo; Sri Yuliani (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
This study aims to evaluate the effectiveness of disability-friendly sexual violence prevention and handling programs in the Sragen Regency, focusing on Gender Focal Point training and Women and Children Protection Service Posts (P4A). This program not only focuses on the implementation of training but also on the overall implementation of the program aimed at increasing the capacity of inclusive services for people with disabilities. The evaluation was conducted using pre-tests and post-tests to assess changes in participants' understanding of sexual violence and the importance of inclusive services. The results showed a significant increase in participants' knowledge after the training, but challenges in implementing disability-friendly services remained, especially related to infrastructure and resource support. This study highlights the importance of a sustainable training approach and provides theoretical insight into how protection services can be more inclusive based on intersectionality theory. Although the study sample is limited, these results provide important insights for developing more responsive protection policies.